Controllability of non-linear models in modelling population dynamics - Klamka, Jerzy (1944- ) (Zielona Góra: Uniwersytet Zielonogórski)
In the paper a mathematical model of two interacting biological populations is considered. U sing techniques adopted from functional analysis such as Schauder's fixed-point theorem, a sufficient condition for local controllability is formulated and proved. Moreover, some additional remarks and comments on controllability problem are given.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka